Insinuations into Attitudes towards Organic Food on Purchase Intentions of Organic Food and Recommendation Intentions - Agustinar Merdekawati Rianto; Whony Rofianto; Anna Riana Putriya (Syntax Idea)
Several factors influence the recurrent purchase attitude of organic food customers in Jabodetabek (the cities of Jakarta, Bogor, Depok, Tangerang, and Bekasi). Under the theories of Consumer Behavior or Perceived Behavior Control and Theory of Planned Behavior, there are 5 endogenous variables that enter into the implications of consumer behavior towards organic food and four exogenous variables on this attitude. Environmental issues, food safety concerns, health consciousness, organic food knowledge, and subjective norms are the five. The remaining four factors are attitude toward organic food, intention to recommend, price barrier, and intention to repurchase organic food. SmartPLS 3.0, based on the PLS SEM formulation, became a tool for calculating the value of 84 respondents in a cross-sectional study. Finally, environmental concerns do not apply to the most recent models. Meanwhile, health concerns, food safety concerns, and price barriers remain minor. There are three constructs that merit additional investigation, in addition to their managerial implications. First, other variables other than this journal must be added for future creation from the producer's standpoint. Second, it is prudent to conduct research for the next development of a certain brand. Third, the following structure can be analyzed over time.